Triflumuron Effects on the Physiology and Reproduction of Rhodnius prolixus Adult Females - Henriques, Bianca Santos (2016)
Fundação Oswaldo Cruz. Instituto Oswaldo Cruz. Laboratório de Bioquímica e Fisiologia de Insetos. Rio de Janeiro, RJ. Brasil.